Suitability of common single circuit boards for sensing and actuating in smart textiles - Guido Ehrmann; Andrea Ehrmann (Communications in Development and Assembling of Textile Products)
Single-board computers and microcontrollers such as Raspberry Pi or Arduino are nowadays used in a broad range of applications. Their relatively low power consumption and low price, compact dimensions and relative ease to program them make them suitable for diverse areas of measuring and controlling various parameters. In the textile area, however, such single-board computers are still less often used than in other projects, in spite of their aforementioned advantages in comparison to other solutions. Here we give an overview of the differences between single-board computers and single-board microcontrollers in general, compare different versions and give examples which projects are reported in the scientific literature, in design or in the maker scene, enabling researchers, designers and makers to decide which future projects necessitate which single circuit boards.